Multiomic traits reveal that critical irinotecan-related core regulator FSTL3 promotes CRC progression and affects ferroptosis - Chengyi Huang; Bufu Tang; Wenjuan Chen; Jinggang Chen; Huojun Zhang; Minghua Bai (Cancer Cell International)
Abstract Background Irinotecan is a widely used chemotherapy drug in colorectal cancer (CRC). The evolution and prognosis of CRC involve complex mechanisms and depend on the drug administered, especially for irinotecan. However, the specific mechanism and prognostic role of irinotecan-related regulators remain to be elucidated. Methods Data from public databases were used to explore the multiomic traits of irinotecan-related regulators through bioinformatics analysis. RT‒qPCR, western blotting, transmission electron microscopy and flow cytometry were used as experimental validations. Results Iriscore (irinotecan-related score) was constructed based on irinotecan-related regulators, and a high iriscore predicted a poor prognosis, poor therapeutic response and the MSS/MSI-L status. Single-cell analysis revealed that FSTL3 and TMEM98 were mainly expressed in CRC stem cells. Potential transcription factors (E2F1, STAT1, and TTF2) and therapeutic drugs (telatinib) that target irinotecan-related regulators were identified. FSTL3 was the core risk irinotecan-related regulator. Some ferroptosis regulators (GPX4, HSPB1 and RGS4) and related metabolic pathways (lipid oxidation and ROS metabolism) were correlated significantly with FSTL3. In vitro, irinotecan inhibited the expression of FSTL3 and ferroptotic defence proteins (GPX4 and SLC7A11), and induced lipid peroxidation and intracellular Fe (2+) ions concentration increased. Conclusions We confirmed that irinotecan-related regulators, especially FSTL3, have effective prognostic value in CRC and speculated that FSTL3 may promote CRC progression and affect ferroptosis, which is beneficial for identifying candidate targeted irinotecan-related regulators and accurate individualized treatment strategies for CRC.